The Influence of Perceived Ease of use, Usefulness, and Security on Gen Z's Interest in using Q-Ris (Quick Response Code Indonesian Standard) as a Payment Method - Harahap, Ridha Anggita; Zoraya, Intan (Formosa Journal of Applied Sciences, 2024)
The development of information technology has caused substantial transformation in various areas of human life. This study aims to investigate the consequences of three main factors, namely perceptions of ease of use, usefulness, and security, on interest in adopting Q-RIS as a payment method. Data was collected through a survey by distributing questionnaires to generation Z aged 17-27 years in 2024 who have used digital wallets with QRIS as a non-cash transaction tool. The number of respondents collected was 107 people, in accordance with the formula of Hair et al. (2017). The data was then analyzed using the Partial Least Squares (PLS) Statistics method. Findings from the research show that perceptions of ease of use, benefits, and security positively and significantly influence interest in adopting QRIS as a payment method.